2017
DOI: 10.1002/brb3.787
|View full text |Cite
|
Sign up to set email alerts
|

Female Parkinson's disease caregivers have much anxiety and depressive symptom

Abstract: ObjectiveParkinson's Disease Caregivers (PDC) play an important role, especially in the medium and advanced phase of the disease for patients’ daily life activities, treatment, and follow‐up. The aim of this study is to attract attention to the factors which place PDC at risk of psychological problems and to give consideration to these factors.Materials and MethodsFirst of all, the 80 participants, who were PDC, filled in the demographic information form. The Hospital Anxiety and Depression Scale (HADS) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“… 31 Similar to this result, a study reported that PDCs had more anxiety and depressive symptoms than their male counterparts. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 Similar to this result, a study reported that PDCs had more anxiety and depressive symptoms than their male counterparts. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A study reported that 32% of PDCs had anxiety symptoms, and 51% of those had depressive symptoms. 8 Recent studies have shown a significant relationship between psychiatric symptoms in PDCs and some symptoms of PD patients like depression. 9 - 13 …”
Section: Introductionmentioning
confidence: 99%
“…Bakım verenlerin anksiyete ve depresyon açısından değerlendirilmesi sonucunda HAD-A skorları kadınlarda erkek bakım verenlere oranla anlamlı ölçüde yüksek elde edildi. Bu sonuç, Parkinson hastası olan fakat kognitif bozulma eşlik etmeyen hastaların bakım verenlerinin araştırıldığı bir başka çalışmada da erkek bakım verenlerin stres düzeyinin kadınlardan daha az olduğu şeklinde vurgulanmış, kadınlarda anksiyete bulgularının erkeklerden daha fazla olduğu gösterilmiştir (25). Çalışmamızda bakım verenlerin yalnızlık düzeyi ile ağrı, anskiyete, depresyon ve bellek yakınmalarının varlığı orta düzeyde ilişkili bulundu.…”
Section: Discussionunclassified
“…Eine Parkinsondiagnose stellt für die individuellen und gemeinsamen Lebensplanungen einen erheblichen Einschnitt dar. Das Belastungserleben ist bei weiblichen pflegenden Angehörigen gegenüber den männlichen Angehörigen zum Teil deutlich erhöht [5,13,12,22]. Selbst wenn die Familiensituation zu Beginn der Erkrankung und während des "drug honeymoons" noch nicht wesentlich verändert ist, nehmen die Anforderungen im weiteren Krankheitsverlauf unweigerlich zu.…”
Section: Belastungen In Einzelnen Krankheitsphasenunclassified